Chad : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2010)
In October 2006, the Chadian government prepared a second National Poverty Reduction Strategy (NPRS2). NPRS2 analyzed poverty in Chad, reviewed the results of the first NPRS and progress toward the Millennium Development Goals (MDGs), defined the strategic pillars of the second strategy, examined two key scenarios for poverty reduction and growth, and described the institutional framework for implementation of the strategy. The government considers NPRS2 as the main instrument for achieving the MDGs in Chad, and therefore the preferred framework for socioeconomic development.